Optimizing Zakat for Rural Community Empowerment: A Case Study of the Al Azhar Zakat Institution in Indonesia - Rohim, Ade Nur; Sahroni, Abdullah (Perencanaan Wilayah dan Kota FT UB, 2026)
This study aims to identify an effective model for rural community empowerment through a qualitative case study of Al Azhar Zakat Institution in Tangerang, Indonesia. This topic is important because zakat has the potential to support rural development, yet limited empirical studies explain how zakat institutions transform charitable funds into sustainable empowerment programs. Primary data were obtained from in-depth interviews with five managerial staff members, while secondary data were collected from institutional reports, company profiles, scholarly journal articles, and other relevant documents. Interview data were analyzed through coding, thematic categorization, and pattern interpretation to formulate the proposed model. The findings from interview data reveal that Al Azhar implements an integrated approach by combining public education, community-based collection, and empowerment-oriented distribution. Meanwhile, documentary data indicate that this model is distinguished by the adoption of digital collection platforms, participatory engagement, and collaborative productive distribution. The novelty of this study lies in the formulation of an integrative rural zakat empowerment model. The study recommends an empirically grounded model for sustainable rural community empowerment. Furthermore, policymakers are encouraged to establish inclusive regulatory frameworks that support cross-sectoral cooperation, thereby advancing sustainable rural development through zakat.